2014
DOI: 10.1590/s1516-635x2014000100005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different levels of dietary crude protein and threonine on performance, humoral immune responses and intestinal morphology of broiler chicks

Abstract: The present study aimed at investigating the effects of different dietary crude protein (CP) and threonine (Thr) levels on the performance, immune responses and jejunal morphology of broiler chicks. A total of 432 broiler chicks were randomly assigned to a 3×3 factorial arrangement of treatments including three different CP dietary levels (90, 95, and 100% of Ross 308 recommendations) and Thr (100, 110, and 120% of Ross specifications) dietary levels. Performance parameters were recorded for the starter (1-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 42 publications
9
48
2
Order By: Relevance
“…These findings are not consistent with those reported by Abassi et al (2014), who showed that the jejunal histological changes observed in broilers fed increasing dietary threonine levels (100, 110, and 120%)promotes an increase in intestinal absorption surface area during the starter, grower, and finisher phases. Those authors reported that threonine influenced the number of structures, intestinal functions, and the number of goblet cells of broilers.…”
Section: Digestible Threonine Levels In the Starter Diet Of Broilerscontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are not consistent with those reported by Abassi et al (2014), who showed that the jejunal histological changes observed in broilers fed increasing dietary threonine levels (100, 110, and 120%)promotes an increase in intestinal absorption surface area during the starter, grower, and finisher phases. Those authors reported that threonine influenced the number of structures, intestinal functions, and the number of goblet cells of broilers.…”
Section: Digestible Threonine Levels In the Starter Diet Of Broilerscontrasting
confidence: 99%
“…Broilers derived from the older breeders also tended to present higher weight gain when supplemented with 1,000mg/kg. Abassi et al (2014) recommended feeding broilers after 12 days of age with at least 10% higher threonine levels than those recommended by the strain's manual to increase weight gain.…”
Section: Digestible Threonine Levels In the Starter Diet Of Broilersmentioning
confidence: 99%
“…The findings of the trial were also in agreement with the observations of Abbasi et al, (2014) (2015) reported that there was no significant difference in feed conversion ratio up to 1.5% unit reduced CP with L-threonine supplementation as compare to control diet, but FCR was significantly poorer when the CP level in the diets decreased at 2.25% According to Ahmed (2014) control diet had better FCR but comparable FCR was also observed in 0.5 and 1% reduced CP diet fed broilers but 1.5% reduced CP diets showed poor FCR,these reports resembles the present study that 2 and 3percent unit CP reduced diet fed birds showed poor FCR. Contrary to our findings in this experiment Hai and Blaha (1998) found no difference in FCR when the protein level of the isocaloric diets was reduced from 20 to 16% crude protein and supplemented with essential amino acids.…”
Section: Resultssupporting
confidence: 89%
“…The fact that the FCR of birds on the 17.0% CP diet with essential amino acids supplementation were still similar (P>0.05) to the FCR values obtained for birds on 23.0% and 20.0% CP diets with essential amino acids supplementation disagreed with previous work where data suggest that after the starter period, reducing dietary CP to 90% of the recommended values had no detrimental impact on broiler performance [18]. Data from the present result indicated that CP can equally be reduced with about 3 points from conventional recommendation [7] without adverse effect on the growth parameters that were investigated in this study.…”
Section: Growth Performancecontrasting
confidence: 86%
“…The lowest significantly different (P<0.05) AND value of 45.65±0.79% was obtained for birds on 11.0% CP diet (diet 6).It has been postulated that the higher crystalline amino acids content of diet may result in better amino acid availability [18] and consequently, the better protein efficiency ratio obtained for some experimental chicks in on very low crude protein diets. It is also ascertained that the availability of free crystalline amino acid is higher than that of amino acids in intact proteins.…”
Section: Nitrogen Utilizationmentioning
confidence: 94%